Impact of land use and vegetation on the formation of thermal islands Case Study: Qainat City - Abdolmajid Ahmadi; ebrahim akbari; javad jamalabadi; maryam alemohammad (تحقیقات کاربردی علوم جغرافیایی)
Awareness of the status of vegetation, land use change and surface temperature in each region, and the timing and location of their changes over time are important for micro and macro planning. In order to make optimal use of land, knowledge of land use changes is necessary, which is usually possible by detecting and predicting land use changes. Measuring the role of researches and researchers has been instrumental in the study of natural resources, especially vegetation, surface temperature and user variations in each location, as well as the availability of information for different times for valuable studies. In this study, ETM and OLI were used to study the process of land use change, vegetation cover, surface temperature, and hazards caused by them in perennial seasons. The results show that the area of use changes over the period 2000-2010 has decreased the area of use of the developed area, agricultural and growing gardens and the area of land and rangelands. Artificial vegetation has risen in aggregate and rangeland lands are showing a decreasing trend. Due to the importance of vegetation and its role in reducing the temperature of the earth's surface, the trend has been decreasing in regions with intensive vegetation and high temperature. Also, in the period from 2010 to 2017, the range was further increased and the city's growth continued sporadically, causing environmental changes and rising temperatures in the city. The change in the city's increased range has increased environmental risks, including the loss of good agricultural land and the increase in the temperature of the city. Due to the fact that most agricultural land is located in the vicinity of the city under cultivation of saffron, which in the warm seasons does not have surface coatings, changes in the type of cultivation can also affect the temperature of the earth.